Industrial Training Approach using GPM P5 Standard for Sustainability in Project Management: A Framework for Sustainability Competencies in the 21st Century - Kartina, Johan; Faiz, Mohd Turan (IOP Publishing, 2016)
Malaysian Engineering Accreditation (Engineering Programme Accreditation Manual, 2007) requires all bachelor degree in engineering programmes to incorporate a minimum of two months industrial training in order for the programme to be accredited by the council. The industrial training has the objective to provide students on the insights of being an engineer at the workplace hence increasing their knowledge in employability skills prior to graduation. However the current structure of industrial training is not able to inculcate good leadership ability and prepare students with sustainability competencies needed in the era of Sustainable Development (SD). This paper aims to study project management methodology as a framework to create a training pathway in industrial training for students in engineering programs using Green Project Management (GPM) P5 standard for sustainability in project management. The framework involves students as interns, supervisors from both university and industry and also participation from NonProfit Organisation (NPO). The framework focus on the development of the student’s competency in employability skills, lean leadership and sustainability competencies using experiential learning approach. Deliverables of the framework include internship report, professional sustainability report using GPM P5 standard and competency assessment. The post-industrial phase of the framework is constructed for students to be assessed collaboratively by the university, industry and the sustainability practitioner in the country. The ability for the interns to act as a change agent in sustainability practices is measured by the competency assessment and the quality of the sustainability report. The framework support the call for developing holistic students based on Malaysian Education Blueprint (Higher Education) 2015-2025 and address the gap between the statuses of engineering qualification to the sustainability competencies in the 21st century in particular by achieving the Sustainability Graduates (SG) attributes outlined in the framework.